Towards policy-relevant science and scientifically informed policy: Political economy of the use of knowledge and research evidence in urban resilience interventions in the Philippines - Contreras, Antonio P. (Animo Repository, 2012)
The objective of our analysis is to better.understand the factors that favor or hinder the use of knowledge and research evidence in the design and implementation of urban resilience measures in selected areas of the Philippines. The research has been conducted adopting the principles of political economy analysis to create an analytical framework that focuses on the specific topic of use of knowledge in policy decision-making processes. There is a growing recognition that politics matter a great deal in development and that technical analysis which, for example, traditionally been applied to the field of natural disaster risk management needs to be complement by a better understanding of the politics that are behind it (see Eaton et al 2010, Faustino and Fabella 2011). Similarly, policy influencing through knowledge and research evidence is a political process as it involves a change in the balance of power between knowledge producers and users (Jones et al 2012). This report contains a background review of definitions of urban resilience with example of interventions to strengthen urban resilience and a list of knowledge product that AusAID has produced on urban resilience and review of main policies and regulations on urban resilience and roles and responsibilities of national government versus LG Us, and a list of main government project/ donors projects and programmes on urban resilience. The data collection has been conducted through focus groups discussions and semi-structured interviews in seven Local Government Units (LGUs): Tabaco City (Albay), Baguio City, and Marikina City (Metro Manila) in Luzon, lloilo City and Cebu City in Central Visayas and Davao City and Cagayan de Oro City in Mindanao. The choice of these case studies areas is linked to the occurrence of national disasters and the experience of decision-making and local planning on climate change/urban resilience. Generally, and in many aspects of public policy, the Philippines has a very well structured policy making at least in theory. There are also a plethora of mechanisms which enable partnerships between and among government agencies, non-government organizations, the private sector and grassroots-based organizations. It has also been noted that there is a high level of social capital prevailing vis-a-vis many policy issues, such as the environment, and in events such as during the occurrence of calamities where civil society actors have been shown to have acted collectively, even autonomous from state instrumentalities. However, and as shown by our field data in disaster risk reduction and management, this somewhat encouraging picture is not matched by robust evidence-based policy making mechanisms and is characterised by a weak link between scientific knowledge on one hand and the policy process on the other. The policy process involves three major actors: the policy makers, usually political and administrative officials engaged in the formulation and implementation of policy decisions; the policy advocates, who are civil society actors acting as pressure groups and interest groups; and the policy analysts, who are the scientists who formulate policy-relevant knowledge and information. The use of scientific knowledge and information would then necessary require an active engagement of and by the policy analysts in the policy process. Hence, the starting point should be the universities and research institutions, as catalyst of change. Researchers and scientists must be made aware that they need to reach out both at the national and local level, even as the administration of academic and research institutions should devise mechanisms to enable and reward work which has direct implications on the active participation of faculty and research staff in the generation and actual utilization of policy-relevant knowledge. This is key to enabling them to become active mediators in bringing science into the policy process. This would also necessarily require the need within universities and research institutions for persons or groups to become active bearers of policy-relevant knowledge, and should be able to represent their interests. There is now opportunity for this to occur, considering that many academic institutions have begun to give priority to a policy-relevant research agenda, providing funding priorities to applied and action researches. The main task is to create a political constituency for science in the policy process. This can be achieved by making science accessible to both the process of policy advocacy and policy making. This can be enabled by translating the technical information which academic researchers generate into popular forms which advocates, politicians and the general public could understand. Grassroots movements must be made aware of the use of science, since they play an important role in creating demand and support systems in the policy process. Politicians should be made aware of and appreciate the use of science. Thus, the scientist has to also now perform the role of an advocate in terms of actively engaging the policy process. Key to this is the equally important challenge of making scientists policy-literate, for them to have an awareness of the political process so that they can be able to navigate its otherwise unfamiliar waters and find strategic points for entry. A more effective way of furthering the agenda of creating a political constituency for science is to foster a collaborative and consultative process even at the time that scientific knowledge is being produced. This would call for a major shift in the way scientific work is done. Contrasted to persons working individually and in isolation in laboratories, this would require the creation of multi-disciplinary teams of scientists actively involving policy makers and advocates in the process, from the point of problem identification to result validation, without compromising the usual integrity of the scientific endeavor. Eventually, the key to realize this theory of change is the role of human agency found in the knowledge and political commitments of people in the three domains of the policy process, as champions for policy-relevant science, and scientifically-informed policy.